Digital-Based Educational Marketing Strategies in Islamic Schools: Constraints and Supporting Factors for Institutional Competitiveness - Nadella Putri; Mahmud MY; Suci Fitriani (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2026)
Abstrak Transformasi digital dan meningkatnya persaingan antar lembaga pendidikan menuntut madrasah untuk mengembangkan strategi pemasaran yang lebih adaptif, efektif, dan bernilai. Dalam konteks lembaga pendidikan Islam, pemasaran digital tidak hanya berfungsi sebagai media promosi, tetapi juga sebagai sarana untuk mengomunikasikan identitas kelembagaan, nilai-nilai pendidikan, dan keunggulan program kepada masyarakat. Namun, banyak madrasah masih menghadapi kendala dalam penerapan pemasaran digital, terutama terkait keterbatasan kompetensi sumber daya manusia, pengelolaan media digital yang belum optimal, dan perencanaan konten promosi yang belum konsisten. Penelitian ini bertujuan untuk menganalisis strategi pemasaran pendidikan berbasis digital di Madrasah Tsanawiyah Darul Arifin Jambi, mengidentifikasi faktor pendukung dan penghambatnya, serta menjelaskan kontribusinya terhadap daya saing lembaga. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara mendalam, observasi, dan studi dokumen dari enam informan yang dipilih secara purposive. Analisis data dilakukan melalui reduksi data, penyajian data, pengodean tematik, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa strategi pemasaran digital melalui media sosial dan komunikasi daring meningkatkan visibilitas lembaga, didukung oleh kepemimpinan visioner, budaya organisasi, dan program unggulan, tetapi masih dibatasi oleh kompetensi digital dan pengelolaan konten yang belum konsisten. Kata Kunci: Pemasaran Pendidikan Digital; Madrasah; Daya Saing Lembaga; Media Sosial; Pendidikan Islam Abstract Digital transformation and increasing competition among educational institutions require madrasahs to develop marketing strategies that are adaptive, effective, and value-driven. In Islamic educational institutions, digital marketing functions not only as a promotional medium but also as a channel for communicating institutional identity, educational values, and program excellence to the public. However, many madrasahs continue to face major challenges in implementing digital marketing, particularly limited human resource competence, suboptimal digital media management, and inconsistent promotional content planning. This study aims to analyze the implementation of digital-based educational marketing strategies at Madrasah Tsanawiyah Darul Arifin Jambi, identify the supporting and inhibiting factors, and explain their contribution to institutional competitiveness. The study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and document analysis from six purposively selected informants. Data analysis was conducted through data reduction, data display, thematic coding, and conclusion drawing. The findings show that digital marketing strategies through social media and online communication increased institutional visibility and public interest. Their implementation was supported by visionary leadership, organizational culture, and flagship programs, but was constrained by limited digital competence and inconsistent content management. These findings indicate that digital-based educational marketing can strengthen institutional competitiveness when aligned with internal institutional capacity and strategic communication. Keywords: Digital Educational Marketing; Madrasah; Institutional Competitiveness; Social Media; Islamic Education